Cell biology - Karp, Gerald (Wiley, 2010)
This edition explores the core concepts of cell biology in considerable depth and presents experimental detail when it helps to explain and reinforce the concepts. The majority of discussions have been modified to reflect the latest changes in the field and it opens each chapter with and illustration that serves as a visual summary.